2019
DOI: 10.1371/journal.pone.0224694
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extra-osseous talotarsal stabilization (EOTTS) to reduce medial knee compartment forces – An in vivo study

Abstract: BackgroundExcessive hindfoot pronation, talotarsal joint (TTJ) instability, has been attributed to an increase in medial knee compartment pathology. Advocacy for hindfoot realignment has been the subject of research. An internal solution for TTJ instability, extra-osseous talotarsal stabilization (EOTTS), exists but its effect on knee forces is unknown. This is the first study to measure the in vivo forces acting within the medial knee compartment before and after EOTTS. We hypothesized that following EOTTS th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Kolodziej et al showed that EOTTS can reduce in vivo forces in the medial knee compartment. This helps illustrate the importance of rearfoot alignment and stabilization in preventing and treating chronic knee pain [10]. Rao et al indicated that an aberrant foot structure has been linked to foot osteoarthritis, as well as osteoarthritis and pain at the knee and hip [33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kolodziej et al showed that EOTTS can reduce in vivo forces in the medial knee compartment. This helps illustrate the importance of rearfoot alignment and stabilization in preventing and treating chronic knee pain [10]. Rao et al indicated that an aberrant foot structure has been linked to foot osteoarthritis, as well as osteoarthritis and pain at the knee and hip [33].…”
Section: Discussionmentioning
confidence: 99%
“…), medial/lateral column osteotomy, and arthrodesis. EOTTS is associated with a reduced risk of post-operative complications and a shorter recovery time while maintaining the positive effects of treatment [2,10,[17][18][19][20]. Therefore, the main working hypothesis in our study was whether physically active patients were able to return to the same level of physical activity after TTJ instability surgeries.…”
Section: Of 12mentioning
confidence: 95%
See 2 more Smart Citations